Analisis Daya Saing Industri Pariwisata Pada Kabupaten Lumajang dan Peningkatan Ekonomi Daerah - Ferdi Wahyu Agustian (Program Studi Ekonomi Pembangunan, 2022)
This study aims to analyze the indicators that determine the competitiveness of the tourism sector in Lumajang Regency. This research was conducted in Lumajang Regency to analyze the competitiveness of the tourism industry in Lumajang Regency. The data analysis used is quantitative descriptive analysis, namely by calculating the tourism competitiveness index by including all 5 indicators of competitiveness from the World Travel and Tourism Council (WWTC) and specializing in Lumajang Regency, namely Human Tourism Indicator (HTI), Price Competitiveness Indicator (PCI), Infrastructure Development Indicator (IDI), Environment Indicator (EI), Openess Indicator (OI). Human Tourism Indicator (HTI) of 3.47, Price Competitiveness Indicator (PCI) of Rp. 2,495,680,784, Infrastructure Development Indicator (IDI) of 213.30, Environment Indicator (EI) of 5.73, and Openness Indicator (OI) of 0.00053. Penelitian ini bertujuan untuk menganalisis Indikator - indikator yang menentukan daya saing sektor pariwisata Kabupaten Lumajang. Penelitian ini dilakukan di Kabupaten Lumajang untuk menganalisis daya saing industri pariwisata Kabupaten Lumajang. Analisis data yang digunakan adalah analisis deskriptif kuantitatif yaitu dengan melakukan penghitungan index daya saing pariwisata dengan memasukkan seluruh indikator daya saing dari World Travel and Tourism Council (WWTC) sebanyak 5 indikator dan mengkhususkan pada Kabupaten Simalungun yaitu Human Tourism Indicator (HTI), Price Competitiveness Indicator (PCI), Infrastructure Development Indicator (IDI), Environtment Indicator (EI), Openess Indicator (OI). Human Tourism Indicator (HTI) sebesar 3,47, Price Competitiveness Indicator (PCI) sebesar Rp. 2.495.680.784, Infrastructure Development Indicator (IDI) sebesar 213,30, Environment Indicator (EI) sebesar 5,73, Dan Openess Indicator (OI) sebesar 0,00053.